2017
DOI: 10.3892/or.2017.5709
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of AKT, ERK and NF-κB by genistein derivative, 7-difluoromethoxyl-5,4′-di-n-octylygenistein, reduces ovarian carcinoma oncogenicity

Abstract: Abstract. Cancer stem cells (CSCs) have central functions in cancer formation and development. Aberrant expression of AKT, ERK and NF-κB signaling pathways have been reported in several types of CSCs. Phytochemicals from dietary compounds possess anti-CSC properties, and have been characterized as promising therapeutic agents for the prevention and treatment of many types of cancers. We previously showed that the newly synthesized genistein derivative, 7-difluoromethoxyl-5,4'-di-n-octylygenistein (DFOG), can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…The context scores of these sites are very high. Additionally, through the TCGA database, it revealed that FoxM1 is overexpressed in most cancer types, and the expression level is also associated with disease prognosis [17][18][19][20][21]. Therefore, in the present study, we associated FoxM1 with miR-320 in human GCA tissues, GCA cell lines and GCA-tumor-bearing mice, and found a negative correlation between miR-320d expression and FoxM1 expression, that is down-regulation of miR-320d could lead to increase FoxM1 expression both in mRNA level and protein level, which promote tumor progression and resulting in poor clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The context scores of these sites are very high. Additionally, through the TCGA database, it revealed that FoxM1 is overexpressed in most cancer types, and the expression level is also associated with disease prognosis [17][18][19][20][21]. Therefore, in the present study, we associated FoxM1 with miR-320 in human GCA tissues, GCA cell lines and GCA-tumor-bearing mice, and found a negative correlation between miR-320d expression and FoxM1 expression, that is down-regulation of miR-320d could lead to increase FoxM1 expression both in mRNA level and protein level, which promote tumor progression and resulting in poor clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…After that, DAB (3.3′-diaminobenzidine tetrahydrochloride, BOSTER, China) was used as chromogen for positive FoxM1 visualization. The resulting slices were analyzed by two independent pathologists, and the IHC results were measured as previously described [17][18][19][20][21].…”
Section: Immunohistochemistry (Ihc) Analysismentioning
confidence: 99%
“…The upregulation of Integrin-ɑ5β1 has been shown to play an important role during tumorigenesis and in the promotion of metastasis in HGSC (Sawada et al 2008;Deng et al 2012;Kiefel et al 2012;Iwanicki et al 2016). Integrin-ɑ5β1 has also been implicated in sphere formation and activation of the AKT and ERK pathways (Casey and Skubitz 2000;Casey et al 2001;Ning et al 2017). The recruitment of Integrin-ɑ5β1 and fibronectin is important for the survival of cell aggregates that lose contact to their primary substratum, by helping to form anchorage to protect from anoikis (Yu et al 2012;Serres et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the mechanisms of action linked with prognosis, let-7 has been involved in several signaling pathways, which could explain its prognostic implication. Suppression of oncogene HMGA2 [ 18 ], inhibition of stemness phenotype [ 19 , 20 ], reduction of phosphorylation of carcinogenic signaling as AKT [ 21 ], influence in immunomodulation [ 22 ], suppression of proliferation [ 23 , 24 ] and control of invasion/migration [ 25 , 26 ] are among the different mechanisms by which let-7 can modulate tumor prognosis.…”
Section: Discussionmentioning
confidence: 99%